2015
DOI: 10.3989/mc.2015.05514
|View full text |Cite
|
Sign up to set email alerts
|

Non-conventional cement-based composites reinforced with vegetable fibers: A review of strategies to improve durability

Abstract: The present review shows the state-of-art on the approachs about improving the processing, physical-mechanical performance and durability of non-conventional fiber-cement composites. The objective of this review is to show some of these strategies to mitigate the degradation of the vegetable fibers used as reinforcement in cost-effective and non-conventional fiber-cement and, consequently, to improve their mechanical and durability properties for applications in the housing construction. Beyond the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 80 publications
0
21
0
7
Order By: Relevance
“…Industrial hemp is becoming a major focus of the green housing segment because of its energy-efficient cultivation, and because hemp-based composites have no negative effects on human health [5]. The excellent physical and mechanical properties of hemp, including low density, high specific stiffness and strength, biodegradability, sound absorption, low processing costs and the ecological suitability of this fast-growing, carbon-negative and non-toxic plant, predispose it for use in building materials (bio-composites) based on inorganic matrices [6], mainly for their application in the housing construction [7]. Traditional building materials, such as concrete, are increasingly being replaced with advanced composite materials in accordance with the principles of sustainability in civil engineering.…”
mentioning
confidence: 99%
“…Industrial hemp is becoming a major focus of the green housing segment because of its energy-efficient cultivation, and because hemp-based composites have no negative effects on human health [5]. The excellent physical and mechanical properties of hemp, including low density, high specific stiffness and strength, biodegradability, sound absorption, low processing costs and the ecological suitability of this fast-growing, carbon-negative and non-toxic plant, predispose it for use in building materials (bio-composites) based on inorganic matrices [6], mainly for their application in the housing construction [7]. Traditional building materials, such as concrete, are increasingly being replaced with advanced composite materials in accordance with the principles of sustainability in civil engineering.…”
mentioning
confidence: 99%
“…The additional fibre-matrix bond in the concrete increases the energy capacity of the concrete by the toughening mechanisms called fibre debonding and frictional sliding associated with fibre pullout (33,34). Furthermore, the steel fibres also arrest the crack opening; such an enhancement mechanism is generally known as the crack bridging effect (13,17,19,20,33,34). The steel fibres bridge across the cracks in the concrete and take part or even all of the stress when subjected to increased loading.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Meanwhile past studies on fibre-reinforced concrete reported significant enhancement of the mechanical properties, cracking resistance and durability compared to the conventional concrete (3,7,8,(13)(14)(15)(16)(17)(18)(19). The other reported advantages of steel fibres in concrete include improving toughness (19), ductility (20), flexural behaviours (21) and impact and blast resistance (5).…”
Section: Research Backgroundmentioning
confidence: 99%
“…The better understanding of this new fiber-cement product is crucial for the manufacture of more sustainable building materials, since cellulosic fibers are biodegradable, renewable, demand low processing energy, and are available around the world at low cost, with a diversity of morphologies and dimensions [24]. In addition, MgO-SiO 2 cements, in contrast to Portland cement which requires high temperatures (about 1450C) during production, demand less energy (750C to obtain reactive MgO from magnesium carbonate [25]) and also allows the reuse of agro-industrial residues to obtain amorphous silica [26], thus becoming a more efficient cement from an environmental point of view.…”
mentioning
confidence: 99%